Studi Evaluasi Kesiapan Mahasiswa Pendidikan Fisika dalam Melaksanakan Praktek Pengalaman Lapangan - Suyidno Suyidno; Joko Siswanto; Sarbaini Sarbaini (Jurnal Penelitian Pembelajaran Fisika, 2019)
PPL has an important contribution in producing physics students as professional teacher candidates. Therefore, theresearch aims to describe the readiness of physics students in implementing PPL in terms of the context, input, process, and product. The research was evaluative descriptive;the initial study was on 10 physics students who had programmed PPL II in 2017; and then continued on 56 physics students who had programmed the PPL II in 2018. Data was collected through the questionnaire instruments and interviews; then data were analyzed with qualitative descriptive.The analysis found that: (1) context aspects, students felt they have understood the concepts and mechanisms of PPL is well; (2) input aspects, used of available resources and strategies implemented by LPTK and school supporting PPL; (3) process aspects, students have been able to plan and implement learning well; and (4) product aspects, students have teacher competency and are able to apply it to success in life and their career in the future. However, LPTK/school still need to overcome the limitations of media/ ICT networks, laboratory equipment, and the similarity of class schedules with PPL. It can be concluded that the implementation of PPL has a positive impact on the readiness of physics students as future professional teachers.